Manual de gestão de pessoas: uma forma de auxiliar o servidor do IFES - Corrêa, Déborah Pinto (2018)
The people management area was created to replace the human resources area by changing organizations' visions of their employees, which were previously perceived as necessary costs and are now considered essential if the objectives of the institutions are to be achieved. In the public sector, despite the bureaucratic and operational bias, the people management area is also very important because it takes care of the server's career and the service it provides, but the extensive legislation and the overload of demands makes the job difficult. In this context, this research was concerned with raising the problems and possible solutions for the sector from the perspective of the professionals who work in the Ifes People Management Board. A research of a qualitative nature was carried out, being used as technical procedures the bibliographical research, the documentary research and the field research in which the instrument of data collect was the exploration of documents and the structured interview. It was identified that one of the major difficulties of the Ifes people management sector is the lack of standardization of procedures, associated with problems in the dissemination of information and that one of the options to minimize them would be the preparation of manuals. As a product of this research, the Ifes server manual was elaborated, clarifying the most frequent doubts regarding the legislation and procedures of the people management area.